Incremental melting in the ureilite parent body: Initial composition, melting temperatures, and melt compositions. (19th April 2020) - Collinet, Max; Grove, Timothy L.
Abstract: Ureilites are carbon‐rich ultramafic achondrites that have been heated above the silicate solidus, do not contain plagioclase, and represent the melting residues of an unknown planetesimal (i.e., the ureilite parent body, UPB). Melting residues identical to pigeonite‐olivine ureilites (representing 80% of ureilites) have been produced in batch melting experiments of chondritic materials not depleted in alkali elements relative to the Sun's photosphere (e.g., CI, H, LL chondrites), but only in a relatively narrow range of temperature (1120 ºC–1180 ºC). However, many ureilites are thought to have formed at higher temperature (1200 ºC–1280 ºC). New experiments, described in this study, show that pigeonite can persist at higher temperature (up to 1280 ºC) when CI and LL chondrites are melted incrementally and while partial melts are progressively extracted. The melt productivity decreases dramatically after the exhaustion of plagioclase with only 5–9 wt% melt being generated between 1120 ºC and 1280 ºC. The relative proportion of pyroxene and olivine in experiments is compared to 12 ureilites, analyzed for this study, together with ureilites described in the literature to constrain the initial Mg/Si ratio of the UPB (0.98–1.05). Experiments are also used to develop a new thermometer based on the partitioning of Cr between olivine and low‐Ca pyroxene that is applicable to all ureilites. The equilibration temperature of ureilites increases with decreasing Al2 O3 and Wo contents of pyroxene and decreasing bulk REE concentrations. The UPB melted incrementally, at different f O2, and did not cool significantly (0 ºC–30 ºC) prior to its disruption. It remained isotopically heterogenous, but the initial concentration of major elements (SiO2, MgO, CaO, Al2 O3, alkali elements) was similar in the different mantle reservoirs.